(untitled) (Academia Science Repository, 2023)
In this article, we will delve deeper into the trends shaping the development of the traditional and modern ecological culture of the Uzbek people. We will explore specific examples of traditional ecological practices, examine the impact of modernization on Uzbekistan’s environment, and highlight the efforts being made to preserve and enhance the country’s ecological heritage. By shedding light on these trends, we hope to inspire a greater appreciation for the Uzbek people’s unique ecological culture and foster a global dialogue on the importance of preserving traditional wisdom in the face of rapid societal changes.